Static Costs vs. Dynamic Benefits of a Minimum Quality Standard under Cournot Competition - Stefan Napel; Gunnar Oldehaver (Aboa Centre for Economics (ACE), 2007)
Imposing a minimum quality standard (MQS) is conventionally regarded as harmful if firms compete in quantities. This, however, ignores dynamic effects. We show that an MQS can hinder collusion, resulting in dynamic welfare gains that reduce and may even outweigh the usual static losses. Verdicts on MQS thus depend even more on the market at hand than has been acknowledged.
Keywords: L41; L51; L15; D43; 330; minimal quality standard; Cournot competition; collusion